2017
DOI: 10.7567/jjap.57.01ad06
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature formation ofc-axis-oriented aluminum nitride thin films by plasma-assisted reactive pulsed-DC magnetron sputtering

Abstract: The low-temperature formation of c-axis-oriented aluminum nitride thin films was demonstrated by plasma-assisted reactive pulsed-DC magnetron sputtering. The effects of the duty cycle at the pulsed-DC voltage applied to the Al target on the properties of AlN films formed via inductively coupled plasma (ICP)-enhanced pulsed-DC magnetron sputtering deposition were investigated. With decreasing duty cycle at the target voltage, the peak intensity of AlN(0002) increased linearly. The surface roughness of AlN films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…We compared relevant literature and found that the FWHM ranged from 0.28 • -0.36 • and decreased with a decrease in duty cycle (20-70%). However, the pulse frequency used in the literature was 100 kHz, which may not be sufficient to achieve the desired plasma activity and concentration [34]. Compared with other studies using asymmetric bipolar pulse deposition of AlN thin films, our results also showed better performance [35].…”
Section: Discussionmentioning
confidence: 58%
“…We compared relevant literature and found that the FWHM ranged from 0.28 • -0.36 • and decreased with a decrease in duty cycle (20-70%). However, the pulse frequency used in the literature was 100 kHz, which may not be sufficient to achieve the desired plasma activity and concentration [34]. Compared with other studies using asymmetric bipolar pulse deposition of AlN thin films, our results also showed better performance [35].…”
Section: Discussionmentioning
confidence: 58%
“…Plasma nitriding treatment can make aluminum and its alloys have excellent physical and chemical properties. [1][2][3] In this regard, various methods have been developed, including plasma immersion ion implantation, 4,5) plasma chemical vapor deposition, [6][7][8] magnetron sputtering, 9,10) and active screen plasma nitriding. 11,12) However, most of these methods demand a vacuum system, which limits the size of the processed material and increases the process complexity.…”
Section: Introductionmentioning
confidence: 99%